Diseño e implementación de un modelo de gestión de compras e inventarios de los materiales de embalaje de espárrago fresco para reducir los costos logísticos de una empresa agroindustrial de La Libertad en el año 2018 - Sedano Rosas, Sheyla (2019)
This research is focused on the management of purchases and inventories of fresh asparagus packaging materials from an agroindustrial company in La Libertad. Its objective is to demonstrate that through the design and implementation of a purchasing and inventory management system it is possible to reduce the logistic costs incurred by the company, and on the occasion, to generate a competitive advantage. To achieve this, it was made a diagnosis of the situation that the company went through at the beginning of the study from a logistic perspective. We identified that the company used the MRP system, but due to the high variation of the sales projections, the company had stock breakdowns or generated over stock. Likewise, it was identified that the purchasing process was bureaucratic and that the company didn’t have established purchasing strategies. Then, materials were classified using the multicriteria ABC technique, and the most relevant materials were identified. For this materials, the replacement point, purchase lot size and safety stock were determined based on the continuous review system with replacement point. The purchasing procedure was modified to turn it into an agile and lower cost process. Likewise, the materials were classified using the Kraljic matrix in leverage, critical and non-critical materials, establishing strategies for each one of these categories. Finally, a quantitative and qualitative analysis of the implementation of purchasing and inventory management was made, and the result of the analysis corroborated the hypothesis of this study. After the implementation of the purchasing and inventory management model, the logistics costs of were reduced in S /. 17 261, 58 which means a decrease of 45,86% with respect to 2017.